A Mycobacterium tuberculosis Cytochrome bd Oxidase Mutant Is Hypersensitive to Bedaquiline - Michael Berney (American Society for Microbiology, 2014)
ABSTRACT The new medicinal compound bedaquiline (BDQ) kills Mycobacterium tuberculosis by inhibiting F1Fo-ATP synthase. BDQ is bacteriostatic for 4 to 7 days and kills relatively slowly compared to other frontline tuberculosis (TB) drugs. Here we show that killing with BDQ can be improved significantly by inhibiting cytochrome bd oxidase, a non-proton-pumping terminal oxidase. BDQ was instantly bactericidal against a cytochrome bd oxidase null mutant of M. tuberculosis, and the rate of killing was increased by more than 50%. We propose that this exclusively bacterial enzyme should be a high-priority target for new drug discovery. IMPORTANCE A major drawback of current TB chemotherapy is its long duration. New drug regimens with rapid killing kinetics are desperately needed. Our study demonstrates that inhibition of a nonessential bacterial enzyme greatly improves the efficacy of the latest TB drug bedaquiline and emphasizes that screening for compounds with synergistic killing mechanisms is a promising strategy.